ANALISIS PELAKSANAAN KEGIATAN PRAKTIKUM BIOLOGI DARING PADA SISWA SMA - Rahma Qonita; Anif Rizqianti Hariz; Erna Wijayanti (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
Online biology practicum during the Covid-19 pandemic requires teachers and students to adapt with online practicum. This study aims to analyze the implementation of online biology practicum activities at SMA N in South Brebes. This is a mixed research that uses data collection techniques through: interviews, observations and questionnaires. The qualitative analysis used the Miles and Huberman model, while the questionnaire data was translated descriptively. The results showed that the online biology practicum at SMA N in South Brebes was carried out only on easy materials and was classified in the bad category. The scores for each factor are: mastery of the material (8.80%), practical implementation (20.50%) and external (14.50%). Weak signal and learning assistance by parents makes a challenge. The solution for this problem is to simplify online biology practicum and choose a simply learning platform. Communication between parents and teachers must be established to control student learning activities.